Analysis of Human-Elephant Conflict in Sri-Lanka by The Win-Win-Win Papakonstantinidis Model - Papakonstantinidis, Leonidas A.; Prakash, T.G Supun Lahiru (International Journal of Economics, Business, and Entrepreneurship, 2019)
Asian Elephants have been revered for centuries and playing an important role in the continent's culture and religion where they habitat. Sri Lanka plays an important role in Asian elephant conservation in accommodating more than 10% of the global Asian elephant population in less than 2% of global Asian elephant range. Human – Elephant conflict (HEC) is a significant component in Socio – economic development in Sri Lanka and conservation of free range elephnats. In this study we attempted to Analysis Human-elephant conflict in Sri-Lanka using the win-win-win Papakonstantinidis model.